Analyze of multipurpose ship main dimensions designed by technical criterion - Denev, Yordan (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The paper deal with impact of technical criterion of ships main dimension. In conceptual design stage for group of multipurpose ships is applied factor of deadweight utilization criterion. Generally this criterion explain the function of the ship in early stages of conceptual design project. Developed conceptual projects of multipurpose ships are with restricted main dimension and deadweight range from 5000 to 8000 tDWT. The purpose of this study is to compare main dimensions of ships developed with technical criterion with this designed with economical criterion.